Phaeanthine and Limacine from Phaeanthus crassipetalus Becc. - Fasihuddin; Shanty V., B. A.; Mohd Sharif, Atan (1991)
Phaeanthus crassipetalus Becc.(Fam: Annonaceae) has been studied. Two major alkaloids have been isolated and characterised based on their spectral information. The alkaloids, phaeanthine (l) and limacine (II), show antibacterial properties against Gram positive and Gram negative bacteria.